Inactivation of iron-sulfur cluster biogenesis regulator SufR in Synechocystis sp. PCC 6803 induces unique iron-dependent protein-level responses - Vuorijoki, Linda; Tiwari, Arjun; Kallio, Pauli; Aro, Eva-Mari (Biochimica et biophysica acta. General subjects, 2017)
Iron-sulfur (Fe-S) clusters are protein-bound cofactors associated with cellular electron transport and redox sensing, with multiple specific functions in oxygen-evolving photosynthetic cyanobacteria. The aim here was to elucidate protein-level effects of the transcriptional repressor SufR involved in the regulation of Fe-S cluster biogenesis in the cyanobacterium Synechocystis sp. PCC 6803. The approach was to quantitate 94 pre-selected target proteins associated with various metabolic functions using SRM in Synechocystis. The evaluation was conducted in response to sufR deletion under different iron conditions, and complemented with EPR analysis on the functionality of the photosystems I and II as well as with RT-qPCR to verify the effects of SufR also on transcript level. The results on both protein and transcript levels show that SufR acts not only as a repressor of the suf operon when iron is available but also has other direct and indirect functions in the cell, including maintenance of the expression of pyruvate:ferredoxin oxidoreductase NifJ and other Fe-S cluster proteins under iron sufficient conditions. Furthermore, the results imply that in the absence of iron the suf operon is repressed by some additional regulatory mechanism independent of SufR. The study demonstrates that Fe-S cluster metabolism in Synechocystis is stringently regulated, and has complex interactions with multiple primary functions in the cell, including photosynthesis and central carbon metabolism. The study provides new insight into the regulation of Fe-S cluster biogenesis via suf operon, and the associated wide-ranging protein-level changes in photosynthetic cyanobacteria. [Display omitted] •Fe-S cluster biogenesis is under complex iron-dependent regulation in Synechocystis.•SufR functions as a repressor of suf operon as demonstrated at protein level.•suf operon is regulated via SufR-independent mechanism under iron deprivation.•SRM revealed various indirect effects on Fe-S cluster proteins in ΔsufR strain.•SufR maintains the expression of NifJ involved in central carbon metabolism.